Marketing desde a pesquisa até a comercialização de tecnologias em universidades: um estudo multicaso - Veroneze, Ricardo Braga (2016)
The main objective of this paper was to investigate the role marketing can assume from research to the commercialization of technologies generated by universities. For this, we propose to describe the marketing practices of four universities of the state of Minas Gerais, Brazil (UFJF, UFLA, UFMG and UFV). A multicase study, of qualitative and exploratory nature, was conducted, based on bibliographic and document researches, and interviews with semistructured script. To the theme, the study proposes a conceptual study model (Framework) of the marketing strategies employed by the federal universities. The paper is structured in the form of articles, divided into three parts. In the presentation, we contextualize the theme, problematics, justifications and general and specific objectives of the research. In addition, we present a theoretical background and a brief summery of the results. In the first article, we seek to systemize the studies on marketing and innovation in universities, in order to identify the dimensions, strategies and practices by means of a systematic review of literature. In the second article, we propose a theoretical model (framework) for investigating the marketing from the research to the commercialization of the technologies in universities, based on a holistic approach of marketing. In the third article, we investigate the marketing actions performed by the universities, based on the proposed framework. By means of the systematic review, it was possible to verify that marketing can be used as a catalyst for market, society and government. With the proposal of the conceptual model, it was possible to investigate and advance with the studies of marketing in the context of the technologies generated by the universities. Empirically, the marketing communication strategies most used by the universities were: digital marketing, participation in events, and publicity. Thus, we suggest new qualitative and quantitative studies for refining and improving the proposed conceptual model (framework).